Analisis Kebutuhan Guru dan Siswa Terhadap Bahan Ajar Digital Berbasis Etnomatematika dengan Model Project-Based Learning - Andang Andang; Arnasari Merdekawati Hadi; Murtalib Murtalib (Supermat : Jurnal Pendidikan Matematika, 2025)
The development of technology and the rich local culture can enhance mathematics learning, especially at SMPN 1 Kota Bima. However, the integration of ethnomathematics with digital technology and project-based learning (PjBL) models is still limited, creating a gap in the utilization of this potential. Most previous research has focused more on the design and implementation of teaching materials, without giving adequate attention to the analysis of the needs of teachers and students. Specific needs related to the integration of Bima's local culture with the PjBL model in mathematics education have not been widely discussed. This study aims to analyze the needs of teachers and students at SMPN 1 Kota Bima regarding digital teaching materials based on ethnomathematics integrated with the PjBL model, as well as to identify barriers and technological preferences influencing the design of these materials. This study uses a qualitative descriptive approach with a needs analysis survey method, involving three mathematics teachers and 50 eighth-grade students. Data were collected through questionnaires, interviews, and observations, and analyzed using descriptive statistics and the Miles and Huberman data analysis model. The analysis results indicate that the majority of students appreciate mathematics learning that is relevant to everyday life, although the connection to local culture is still limited. The use of technology in mathematics learning is also relatively low, while the application of the PjBL model increases student participation, despite challenges in its implementation. These findings suggest the need for the development of digital teaching materials that integrate Bima's local culture within the context of mathematics education. In addition, training support for teachers and improved access to technology are also crucial to enhance student engagement and learning effectiveness.